FACTORS AFFECTING VISUAL ACUITY IN ADOLESCENT GADGET USERS - Mikawati Mikawati; Lisnawati Lisnawati; Suriyani Suriyani; Nofianti Nofianti; Sari Narulita (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
The eye is one of the senses that is very important for humans to absorb visual information. Incorrect use of gadgets, such as excessive frequency of gadget use, improper positioning, and poor lighting intensity, will have an impact on reducing visual acuity. The purpose of this study is to determine the factors that influence the occurrence of decreased visual acuity in adolescents using gadgets at SMP Negeri 2 Makassar. This study is an analytical observational study with a cross-sectional approach conducted at SMP Negeri 2 Makassar on August 22–24, 2022. The total population of seventh grade students at SMP Negeri 2 Makassar was 216. Sampling was done in this study using the random simple sampling technique, with the number of samples that meet the inclusion criteria reaching as many as 77 students. Gender obtained a p value of 0.059, the use of glasses obtained a p value of 0.334, and the type of gadget obtained a p value of 1,000. The length of playing gadgets obtained a p value of 0.000, and the position of playing gadgets had a p value of 0.415. It can be concluded that the length of use of gadgets is a factor that affects the decline in visual acuity. From the results of research on factors affecting visual acuity in adolescent gadget users at SMP Negeri 2 Makassar in 2022, it can be concluded that there is no relationship between age, gender, use of glasses, type of gadget, and position of playing gadgets with decreased visual acuity, and there is a relationship between the duration of playing gadgets > 4 hours with decreased visual acuity (p 0.000) in adolescent age children at SMP Negeri 2 Makassar. to the school to conduct routine sharp vision checks at school in collaboration with the local health center.